The Danish patient safety experience: the Act on Patient Safety in the Danish health care system (Italian Journal of Public Health, 2005)
This paper describes the process that lead to the passing of the Act for Patient Safety in the Danish health care system, the contents of the act and how the act is used in the Danish health care system.The act obligates frontline health care personnel to report adverse events, hospital owners to act on the reports and the National Board of Health to communicate the learning nationally.The act protects health care providers from sanctions as a result of reporting. In January 2004, the Act on Patient Safety in the Danish health care system was put into force. In the first twelve months 5740 adverse events were reported.The reports were analyzed locally (hospital and region), anonymized and then sent to the National Board of Health. The Act on Patient Safety has driven the work with patient safety forward but there is room for improvement. Continuous and improved feedback from all parts of the system is essential to maintain the level of reporting.
Keywords: Patient safety; adverse event; Danish pilot study; Danish Society for Patient Safety; reporting system; learning system